2011
DOI: 10.1158/1055-9965.epi-11-0341
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine RANTES Promoter Dimorphisms and Hepatocellular Carcinoma Occurrence in Patients with Alcoholic or Hepatitis C Virus–Related Cirrhosis

Abstract: Background: This study explores the influence of two functional genetic polymorphisms in the regulated on activation in normal T-cell expressed and secreted (RANTES) promoter on the risk of hepatocellular carcinoma (HCC) occurrence in patients with alcoholic or Hepatitis C Virus (HCV)-related cirrhosis.Methods: RANTES C-28G and G-403A promoter dimorphisms and RANTES serum levels were assessed in 243 HCV-infected patients and 253 alcoholic patients, included at the time of diagnosis of cirrhosis and prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
1
10
1
1
Order By: Relevance
“…Although the connection between RANTES polymorphism and chemokine serum concentration and some malignancies has been demonstrated previously, we failed to confirm that phenomenon in BCC [35, 36]. Little is known about the role of RANTES in BCC.…”
Section: Discussioncontrasting
confidence: 54%
“…Although the connection between RANTES polymorphism and chemokine serum concentration and some malignancies has been demonstrated previously, we failed to confirm that phenomenon in BCC [35, 36]. Little is known about the role of RANTES in BCC.…”
Section: Discussioncontrasting
confidence: 54%
“…These genetic traits are capable of modulating several biological pathways involved in hepatocarcinogenesis, such as inflammation [63,64], oxidative stress [65,66], and iron [67,68] or lipid metabolism [69]. In this setting, other genetic modifiers of lipid turnover seem to impact HCC risk in association with PNPLA3 genotype.…”
Section: Pnpla3 In the Complex Genetic Heterogeneity Influencing Livementioning
confidence: 99%
“…Alcohol is one of the major risks of liver injury and has been considered as a promoter for HCC (26). It has been found that patients with alcoholic cirrhosis and bearing two copies of the RANTES G-403 variant (2G-403 genotype) had a higher rate of HCC occurrence compared with patients carrying at least one RANTES A-403 allele (27). AFP has been reported to be higher in patients with HCC arising from chronic viral conditions compared to those with alcoholic liver disease (28).…”
Section: Introductionmentioning
confidence: 99%